Facilitators and Barriers Related to Complementary Feeding Practices among Mothers of Children Under 2 Years of Age in Karachi - TUBA RASHEED,; FERRUKH ZEHRAVI,; MIRZA TAHA BAIG,; SADIA,; SIMRAN,; SHEEZA NAZ,; TAZEEN SAEED,; MUHAMMAD SULEMAN KHAN,; ABDUL SAMI, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To identify the underlying Facilitators and Barriers influencing Complementary feeding practices among mothers of children under 2 years of age in Karachi and to determine the level of Knowledge, attitudes and practices of Complementary feeding practices among mothers of children under 2 years of age in Karachi. Methods: A cross-sectional study was conducted in Karachi, Pakistan, from September 2022 to February 2023, focusing on complementary feeding practices among mothers of under-two-year-olds. A self-administered questionnaire was administered to participants, identifying facilitators and barriers. The study included mothers and children under 24 months old, lactating or non lactating, who have delivered a child or have children up to 2 years old. Data was analyzed using SPSS and Chi-square test to determine associations between variables. Results: The majority of the mothers displayed poor knowledge and the practices regarding complementary feeding were found to be fair. With regards to barriers and facilitators of complementary feeding practices, mother’s and father’s education were significant facilitators while level of attitude was found to be a significant barrier which influenced feeding practices among mothers. Conclusion: Mothers of children under 2 years old, especially non-literate ones, have poor complementary feeding knowledge and practices. Global health goals include reducing child malnutrition through supplemental feeding. Reduce child morbidity and death with complementary feeding education that changes behavior. Key words: Complementary feeding practices, Facilitator, Barriers